The philosophy of "makdanakan" in the community settlement of Bontang Kuala Urban Village, Bontang City (ARTEKS : Jurnal Teknik Arsitektur, 2023)
The Bontang Kuala urban village was originally a settlement of the Bajau tribe, which has a unique culture and tradition based on the local wisdom values in it. This study aimed to determine the concept that serves as the bottom-line for the unique spatial patterns of settlements formed by using a qualitative inductive method with a phenomenological approach. Study results showed that the formation of residential spaces for the people of Bontang Kuala urban village is based on the “makdanakan” philosophy. This philosophy gives both physical and non-physical influences in the formation of residential spaces.
Keywords: Bajau tribe; Makdanakan philosophy; Phenomenology; Settlement